2018
DOI: 10.1242/jcs.221853
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of actin-based apical structures on epithelial cells

Abstract: Cells of transporting epithelia are characterized by the presence of abundant F-actin-based microvilli on their apical surfaces. Likewise, auditory hair cells have highly reproducible rows of apical stereocilia (giant microvilli) that convert mechanical sound into an electrical signal. Analysis of mutations in deaf patients has highlighted the critical components of tip links between stereocilia, and related structures that contribute to the organization of microvilli on epithelial cells have been found. Ezrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 144 publications
(180 reference statements)
3
84
0
Order By: Relevance
“…Thus, while the increase in width in fused and giant, elongated stereocilia that subsequently develop is likely a result of accumulation of the existing filaments into the fusing stereocilia, the increase in length is presumably due to growth of the actin filaments. Stereocilia grow in length during development by addition of actin monomers to the apical tips of the filaments and are maintained during life by a slow turnover of actin in a small compartment at that tip (Drummond et al, ; McGrath, Roy, & Perrin, ; Narayanan et al, ; Pelaseyed & Bretscher, ). The elongation of stereocilia therefore suggests that the machinery for trafficking actin to the tips of stereocilia is still active, providing additional evidence for the “viability” of the hair cells upon which fused and elongated stereocilia are present.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the increase in width in fused and giant, elongated stereocilia that subsequently develop is likely a result of accumulation of the existing filaments into the fusing stereocilia, the increase in length is presumably due to growth of the actin filaments. Stereocilia grow in length during development by addition of actin monomers to the apical tips of the filaments and are maintained during life by a slow turnover of actin in a small compartment at that tip (Drummond et al, ; McGrath, Roy, & Perrin, ; Narayanan et al, ; Pelaseyed & Bretscher, ). The elongation of stereocilia therefore suggests that the machinery for trafficking actin to the tips of stereocilia is still active, providing additional evidence for the “viability” of the hair cells upon which fused and elongated stereocilia are present.…”
Section: Discussionmentioning
confidence: 99%
“…The group comprises EZR and HNRNPH1 (Cytoscape) and CD2AP (MapoftheCell). It is widely accepted that ezrin participates in anchoring membrane proteins to the cortical actin network [118]. Nuclear localization of ezrin was also reported, however, the role of nuclear ezrin is not yet deciphered [119].…”
Section: Resultsmentioning
confidence: 99%
“…Both the microvilli and the much longer stereocilia have backbones that are composed of bundles of actin filaments (Brown & McKnight, 2010; Pelaseyed & Bretscher, 2018). The actin filaments are tethered to the cell membrane by actin‐binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have shown that the apical borders of the epithelial cells in the vas deferens are covered by microvilli or stereocilia (Francavilla et al, 1987; Hamilton & Cooper, 1978; Höfer & Drenckhahn, 1996; Rodriguez & Bustos‐Obregón, 1993). Both microvilli and stereocilia are cell projections that have backbones composed of actin filament bundles (Pelaseyed & Bretscher, 2018). In epithelial cells, a network of actin filaments lies underneath the membrane providing structural support for the membrane.…”
Section: Introductionmentioning
confidence: 99%